Environmental processes affecting the San Antonio bay and its adyancent areas (province of Río Negro). (Huellas, 2015)
Natural processes together with human activities represent necessary variables for the changes affecting different environments in coastal areas. The aim of this paper is to identify, through the use of geo-technologies, the environmental processes that affect the natural area in the San AntonioBay, which includes the cities of San Antonio Oeste, San Antonio Este and Las Grutas. Satellite images (Spot and Landsat 5 and 7) of different tide states, aerial photographs, topographic and nautical charts were processed. All the information obtained was systematized and integrated in a GIS (Geographic Information System). The morphology of the area under study consists of tidal plains and tidal channels, spits, dunes and cliffs. This ecosystem undergoes natural processes such as: eutrophication in the channel of La Mareain San Antonio Oeste, sedimentation of tidal channels in San Antonio Este and in the Villarino peninsula, accretion in coastal areas and sandbanks displacement. Likewise, the urban growth of San Antonio Oeste directly affects the natural environment of the protected area as well as the industrial activities and urban wastes.
Keywords: geo-tecnologies - environmental processes - San Antonio Bay- GIS